PENGARUH PROFITABILITAS, DEWAN KOMISARIS INDEPENDEN, LEVERAGE, INTENSITAS ASET TETAP TERHADAP TARIF PAJAK EFEKTIF PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Juhli Edi Simanjuntak; Destriana Helda (Bajang Institute, 2023)
This study aims to determine whether there is an influence arising from profitability, independent board of commissioners, leverage, fixed aset intensity on effective tax rates in manufactur companies listed on the Bursa Efek Indonesia (BEI). The sample was determined by purposive sampling, in order to obtain a total sample of 41 companies. The method that used in this research is a quantitative method. The results of this research indicate that profitability has no significant effect on the effective tax rate, the Independent Board of Commissioners has no significant effect on the effective tax rate, Leverage has no significant effect on the effective tax rate and the intensity of fixed asets does not have a significant effect on the effective tax rate. The results of this research indicate that simultaneously the variables Profitability, Independent Board of Commissioners, Leverage, and Fixed Asets Intensity do not simultaneously influence the Effective Tax Rate